2016
DOI: 10.1038/am.2016.76
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic-field-induced spontaneous superlattice formation via spinodal decomposition in epitaxial strontium titanate thin films

Abstract: Periodically structured nanomaterials such as superlattices have a wide range of applications. Many electronic devices have been fabricated from these materials. The formation of spontaneous layer structures using epitaxial growth has also been reported for many compound semiconductors but for very few ceramics. We demonstrate that strontium titanate (Sr-Ti-O) thin films having an A-site excess composition in the perovskite structure deposited by pulsed laser deposition under a magnetic field show a spontaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 47 publications
0
35
0
Order By: Relevance
“…On the other hand, when the growth rate is higher, the composition variation occurs in the direction normal to the film plane. This phenomenon, called surface-directed spinodal decomposition (SDSD), generates the superlattice structure in the film after phase separation [17,29]. In our previous study, we reported the superlattice structure formation through SDSD in SrTiO 3 films grown by Dynamic Aurora PLD [17].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…On the other hand, when the growth rate is higher, the composition variation occurs in the direction normal to the film plane. This phenomenon, called surface-directed spinodal decomposition (SDSD), generates the superlattice structure in the film after phase separation [17,29]. In our previous study, we reported the superlattice structure formation through SDSD in SrTiO 3 films grown by Dynamic Aurora PLD [17].…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon, called surface-directed spinodal decomposition (SDSD), generates the superlattice structure in the film after phase separation [17,29]. In our previous study, we reported the superlattice structure formation through SDSD in SrTiO 3 films grown by Dynamic Aurora PLD [17]. Here, the composition wave propagates in the vertical direction [17,28,29].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations